DEVELOPMENT AND CHARACTERIZATION OF FISH MEATBALLS PREPARED WITH MECHANICALLY SEPARATED MEAT OF AMAZON HYBRID SORUBIM COATED WITH SAFFLOWER FLOUR AT DIFFERENT GRANULOMETRIES - Fonseca, Gustavo; Cavenaghi-Altemio, Angela Dulce (Food and Feed Research, 2025)
The aim of this work was to develop a food alternative for consumers with celiac disease. Thus, fish meatballs were prepared from mechanically separated meat of Amazon hybrid sorubim (Pseudoplatystoma reticulatum x Leiarius marmoratus) and breaded with gluten-free safflower flour at two granulometries and characterized. Three treatments were evaluated: wheat flour (control) (T1), safflower at mesh 8 (T2), and safflower at mesh 14 (T3). Characterization was conducted through chemical, physical, microbiological, and sensory analyses. The moisture content of T1 (67.89%) was significantly higher (p0.05) between treatments for protein content (10.85-11.60%). All treatments differed from each other in lipid and ash contents, the prior being higher for T2 (15.89%) and the former for T1 (1.53%). For crude fiber content, there was no difference (p>0.05) between T2 and T3, but statistically higher (p